Metabolomic- and Molecular Networking-Based Exploration of the Chemical Responses Induced in Citrus sinensis Leaves Inoculated with Xanthomonas citri - Saldanha, Luiz Leonardo; Allard, Pierre-Marie; Dilarri, Guilherme; Codesido, Santiago; González-Ruiz, Víctor; Queiroz, Emerson Ferreira; Ferreira, Henrique; Wolfender, Jean-Luc (American Chemical Society (ACS), 2022)
Citrus canker, caused by the bacterium Xanthomonas citri subsp. citri (X. citri), is a plant disease affecting Citrus crops worldwide. However, little is known about defense compounds in Citrus. Here, we conducted a mass spectrometry-based metabolomic approach to obtain an overview of the chemical responses of Citrus leaves to X. citri infection. To facilitate result interpretation, the multivariate analyses were combined with molecular networking to identify biomarkers. Metabolite variations among untreated and X. citri-inoculated Citrus samples under greenhouse conditions highlighted induced defense biomarkers. Notably, the plant tryptophan metabolism pathway was activated, leading to the accumulation of N-methylated tryptamine derivatives. This finding was subsequently confirmed in symptomatic leaves in the field. Several tryptamine derivatives showed inhibitory effects in vitro against X. citri. This approach has enabled the identification of new chemically related biomarker groups and their dynamics in the response of Citrus leaves to Xanthomonas infection.
Keywords: biotic stress; citrus canker; pathogen-induced metabolites; sweet orange; tryptamines